2013
DOI: 10.1080/00480169.2013.817294
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of thermotolerantCampylobacterspp. at different stages of the poultry meat supply chain in Argentina

Abstract: The proportions of Campylobacter-positive samples found in this preliminary study indicate that a large proportion of the cases of human gastroenteritis in Argentina may be due to this pathogen. Human cases of gastroenteritis should be studied in greater detail and measures should be developed to reduce the proportion of poultry products that are contaminated by Campylobacter species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…From Brazil and Costa Rica, 100.0% respectively 80.0% of the flocks were reported to be positive for Campylobacter when ceca samples were studied (Giombelli and Gloria, 2014 ; Zumbaco-Gutiérrez et al, 2014 ). On the other hand, in Argentina and Chile Campylobacter was found in 33.3% of samples (Rivera et al, 2011 ; Zbrun et al, 2013a ) while in Peru Tresierra-Ayala et al ( 1995 ) reported a prevalence of 35%. Other tropical countries such as Vietnam and South Africa have reported a prevalence of 31.9 and 14.2% respectively (Jonker and Picard, 2010 ; Carrique-Mas et al, 2014 ).…”
Section: Discussionmentioning
confidence: 98%
“…From Brazil and Costa Rica, 100.0% respectively 80.0% of the flocks were reported to be positive for Campylobacter when ceca samples were studied (Giombelli and Gloria, 2014 ; Zumbaco-Gutiérrez et al, 2014 ). On the other hand, in Argentina and Chile Campylobacter was found in 33.3% of samples (Rivera et al, 2011 ; Zbrun et al, 2013a ) while in Peru Tresierra-Ayala et al ( 1995 ) reported a prevalence of 35%. Other tropical countries such as Vietnam and South Africa have reported a prevalence of 31.9 and 14.2% respectively (Jonker and Picard, 2010 ; Carrique-Mas et al, 2014 ).…”
Section: Discussionmentioning
confidence: 98%
“…A total of 152 thermotolerant Campylobacter were isolated from six poultry meat supply chains in Santa Fe region in Argentina (Zbrun et al, 2013). The stages sampled in each poultry meat chain were: a) hens from breeder flocks, b) broilers in flocks (aged <1 wk and >5 wk), c) chickens at the slaughterhouse, and d) chicken meat at the retail market.…”
Section: Collection Of Campylobacter Isolatesmentioning
confidence: 99%
“…Both between-and within-flock prevalence in Argentina was estimated based on data obtained by our group in different samplings (Rossler et al, 2020;Zbrun et al, 2013;Zbrun et al, 2017Zbrun et al, , 2021. The median estimate of transmission coefficient (β) was 1.54 ± 1.03 day -1 .…”
Section: Transmission Dynamics Of Thermotolerant Campylobacter In Com...mentioning
confidence: 99%
“…The vertical transmission of Campylobacter is not fully established, but current knowledge indicates that it has a very low probability of occurrence in poultry farms (Zhang and Sahin, 2020). In an observational study conducted by our group (Zbrun et al., 2013), we isolated Campylobacter in broiler birds that were less than one week of age (5–7 days). Humphrey et al.…”
Section: Introductionmentioning
confidence: 99%